Figure 8. Culeolus suhmi Herdman, 1881 in Deep-water ascidians from the North Atlantic (RV Academic Keldysh, cruise 46 and 49) - Sanamyan, K. E.; Sanamyan, N. P. (Zenodo, 2005)
Figure 8. Culeolus suhmi Herdman, 1881. (A) Intact specimen (whole stalk not shown); (B) specimen opened along ventral mid line; branchial sac removed to show gut, gonads and muscles. : Published as part of Sanamyan, K. E. & Sanamyan, N. P., 2005, Deep-water ascidians from the North Atlantic (RV Academic Keldysh, cruise 46 and 49), pp. 2005-2021 in Journal of Natural History 39 (22) on page 2016, DOI: 10.1080/00222930400026969, http://zenodo.org/record/5215226